Early Cretaceous non-marine bivalves from the Cameros and Basque-Cantabrian basins of Spain - Delvene, G.; Araujo, R. (Journal of Iberian Geology, 2009)
Large unionids from the Weald facies of northern Spain are described. Three hundred seventeen specimens belonging to the Order Unionoida have been studied. Two species from the family Margaritiferidae were identified from the Cameros Basin. Margaritifera idubedae (Palacios and Sánchez, 1885) was recorded from the Urbión Group (Hauterivian-Barremian in age), being a very frequent bivalve in these fluvial sediments. Margaritifera valdensis (Mantell, 1844) was collected from the Enciso Group (Aptian in age) and is an uncommon bivalve in this lacustrine environment. A new genus with a new species called Protoanodonta conchae Delvene and Araujo, family Unionidae, is described from the Basque-Cantabrian Basin. Samples came from the Viviparus Bed Member (Vega de Pas Formation, Hauterivian-Barremian), interpreted as freshwater environment lacustrine in origin.